A melatonin‐based fluorescence method for the measurement of mitochondrial complex III function in intact cells. Issue 4 (17th August 2013) - Fu, Jian‐Liang; Zhang, Hong‐Mei; Zhang, Hua; Kamat, Amrita; Yeh, Chih‐Ko; Zhang, Bin‐Xian
Abstract Mitochondrial complex III (MC‐3) plays a pivotal role in electron transfer and oxidative phosphorylation. Impaired MC‐3 functions may contribute to a variety of diseases by interrupting normal bioenergetics and increasing reactive oxygen production and oxidative stress. Currently, MC‐3 function is assessed by measuring the cytochrome c reductase activity spectrophotometrically in isolated mitochondria or MC‐3. The cytoplasmic microenvironment critical for mitochondrial complex functions may be depleted during these isolation processes. The development of a reliable method to measure MC‐3 activities in intact cells or tissues is highly desirable. This report describes a novel fluorescence‐based method to assess MC‐3 functions, i.e., Qi site electron transfer, in the intact cells. Human mesangial and teratocarcinoma NT2 cells were used to demonstrate that melatonin‐induced oxidation of 2′, 7′‐dichlorodihydrofluorescein (H2DCF) was inhibited by antimycin A, the MC‐3 Qi site‐specific inhibitor, but not by myxothiazol, the MC‐3 Qo site‐specific inhibitor, nor rotenone, the mitochondrial complex I inhibitor. These results indicate that melatonin‐induced oxidation of H2DCF is reflecting MC‐3 Qi site electron transfer activities. Modifying structures of the side groups at the R3 and R5 positions of the indole ring of melatonin diminished its efficacy for inducing H2DCF oxidation, suggesting a specific interaction of melatonin with the MC‐3 Qi site. These results suggest that the fluorogenic property of melatonin‐induced H2DCF oxidation provides a MC‐3 Qi site electron transfer‐specific measurement in intact cells. Interestingly, using this method, the Qi site electron transfer activity in transformed or immortalized cells was found to be significantly higher than the nontransformed cells.